2022
DOI: 10.3389/fonc.2022.901951
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Rewiring in Glioblastoma Cancer: EGFR, IDH and Beyond

Abstract: Glioblastoma multiforme (GBM), a highly invasive and incurable tumor, is the humans’ foremost, commonest, and deadliest brain cancer. As in other cancers, distinct combinations of genetic alterations (GA) in GBM induce a diversity of metabolic phenotypes resulting in enhanced malignancy and altered sensitivity to current therapies. Furthermore, GA as a hallmark of cancer, dysregulated cell metabolism in GBM has been recently linked to the acquired GA. Indeed, Numerous point mutations and copy number variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 164 publications
0
6
0
Order By: Relevance
“…It has been reported that the cuproptosis gene is associated with the prognosis of triple-negative breast cancer [ 19 ]. In addition, it has been found that grade 4 diffuse gliomas are related to iron death, metabolism, and apoptosis [ [20] , [21] , [22] ]. However, the relationship between cuproptosis and grade 4 diffuse gliomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the cuproptosis gene is associated with the prognosis of triple-negative breast cancer [ 19 ]. In addition, it has been found that grade 4 diffuse gliomas are related to iron death, metabolism, and apoptosis [ [20] , [21] , [22] ]. However, the relationship between cuproptosis and grade 4 diffuse gliomas remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of distinct metabolic routes also depend on the GBM genomic and epigenomic landscape, as specific mutations are associated with typical metabolic pathways, whilst perturbations in chromatin-remodeling enzyme activity may impact metabolic changes and vice versa. These specific topics have been extensively reviewed elsewhere [ 124 , 125 , 126 ].…”
Section: Gbm Metabolismmentioning
confidence: 99%
“…Notably, Novartis’s IDH305 focuses on IDH1 mutations, and ongoing trials in gliomas and other cancers with IDH1 R132 mutations are active (NCT02381886). Furthermore, both Forma Therapeutics’ FT2102 and Bayer’s BAY1436032 target IDH1 R132 tumors (R132X for BAY1436032), with trials actively enrolling patients across several tumor types, including GBM (NCT03684811 and NCT02746081) [ 162 ].…”
Section: Recent Advancements In Metabolic Reprogramming Of Gbm and Gscsmentioning
confidence: 99%